The associations between traumatic experiences and subsequent onset of a substance use disorder: Findings from the World Health Organization World Mental Health surveys. (1st November 2022) - Degenhardt, Louisa; Bharat, Chrianna; Glantz, Meyer D.; Bromet, Evelyn J.; Alonso, Jordi; Bruffaerts, Ronny; Bunting, Brendan; de Girolamo, Giovanni; de Jonge, Peter; Florescu, Silvia; Gureje, Oye; Haro, Josep Maria; et al.
Abstract: Aim: Exposure to traumatic events (TEs) is associated with substance use disorders (SUDs). However, most studies focus on a single TE, and are limited to single countries, rather than across countries with variation in economic, social and cultural characteristics. We used cross-national data to examine associations of diverse TEs with SUD onset, and variation in associations over time. Methods: Data come from World Mental Health surveys across 22 countries. Adults (n = 65, 165) retrospectively reported exposure to 29 TEs in six categories: "exposure to organised violence"; "participation in organised violence"; "interpersonal violence"; "sexual-relationship violence"; "other life-threatening events"; and those involving loved ones ("network traumas"). Discrete-time survival analyses were used to examine associations with subsequent first SUD onset. Results: Most (71.0%) reported experiencing at least one TE, with network traumas (38.8%) most common and exposure to organised violence (9.5%) least. One in five (20.3%) had been exposed to sexual-relationship violence and 26.6% to interpersonal violence. Among the TE exposed, lifetime SUD prevalence was 14.5% compared to 5.1% with no trauma exposure. Most TE categories (except organised violence) were associated with increased odds of SUD. Increased odds of SUD were also found following interpersonal violence exposure across all age ranges (ORs from 1.56 to 1.78), and sexual-relationship violence exposure during adulthood (ORs from 1.33 to 1.44), with associations persisting even after >11 years. Conclusion: Sexual and interpersonal violence have the most consistent associations with progression to SUD; increased risk remains for many years post-exposure. These need to be considered when working with people exposed to such traumas. Highlights: Most respondents experienced at least one lifetime traumatic experience (71.0%). Traumas involving loved ones were most common (38.3%). Lifetime substance use disorder more common among those with trauma (14.5% v. 5.1%). Most trauma groups associated with increased odds of substance use disorder onset. Interpersonal- & sexual-relationship violence associations persist long after first exposure.